2018
DOI: 10.3390/su10114285
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Carbon Dioxide Sink and Methane Source under Extreme Drought Condition in an Alpine Peatland

Abstract: Potential changes in both the intensity and frequency of extreme drought events are vital aspects of regional climate change that can alter the distribution and dynamics of water availability and subsequently affect carbon cycles at the ecosystem level. The effects of extreme drought events on the carbon budget of peatland in the Zoige plateau and its response mechanisms were studied using an in-field controlled experimental method. The results indicated that the peatland ecosystem of the Zoige plateau functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 55 publications
(74 reference statements)
1
20
0
Order By: Relevance
“…Since the latter two processes make the greatest contribution to the CH 4 flux in peatlands (Whalen, Reeburgh, and Sandbeck 1990;Lai 2009), the changes in peat aeration, compaction and temperature as well as nutrient level and vegetation cover can substantially influence CH 4 emissions (Berger et al 2018). Lowered water levels reduce CH 4 emissions by decreasing the abundance of methanogens and CH 4 production and increasing CH 4 oxidation levels, while raised water levels have a higher potential of anaerobic CH 4 production (Frenzel and Karofeld 2000;Roulet 2000; The relationship of CH 4 flux and peatland flooding is similar in peatlands in different regions as verified by both field observations (Roulet and Moore 1995;Nykanen et al 1998;Bellisario et al 1999;Chimner and Cooper 2003a;Strack, Waddington, and Tuittila 2004;Jauhiainen et al 2005;Strack, Waller, and Waddington 2006b;Myers-Smith et al 2007;Moore et al 2011;Yrjala et al 2011;Blodau and Siems 2012;Ballantyne et al 2014;Chimner et al 2016;Laine et al 2019b;Zhang et al 2019;Planas-Clarke et al 2020) and manipulation experiments (Dise, Gorham, and Verry 1993;Funk et al 1994;Aerts and Ludwig 1997;Blodau, Basiliko, and Moore 2004;Strack and Waddington 2007;Turetsky et al 2008;Chivers et al 2009;Dinsmore et al 2009;Laine et al 2009;Pearson et al 2015;Olefeldt et al 2017;Kang et al 2018;…”
Section: Effects Of Water Level Alteration On Ch 4 Emissionsmentioning
confidence: 84%
See 1 more Smart Citation
“…Since the latter two processes make the greatest contribution to the CH 4 flux in peatlands (Whalen, Reeburgh, and Sandbeck 1990;Lai 2009), the changes in peat aeration, compaction and temperature as well as nutrient level and vegetation cover can substantially influence CH 4 emissions (Berger et al 2018). Lowered water levels reduce CH 4 emissions by decreasing the abundance of methanogens and CH 4 production and increasing CH 4 oxidation levels, while raised water levels have a higher potential of anaerobic CH 4 production (Frenzel and Karofeld 2000;Roulet 2000; The relationship of CH 4 flux and peatland flooding is similar in peatlands in different regions as verified by both field observations (Roulet and Moore 1995;Nykanen et al 1998;Bellisario et al 1999;Chimner and Cooper 2003a;Strack, Waddington, and Tuittila 2004;Jauhiainen et al 2005;Strack, Waller, and Waddington 2006b;Myers-Smith et al 2007;Moore et al 2011;Yrjala et al 2011;Blodau and Siems 2012;Ballantyne et al 2014;Chimner et al 2016;Laine et al 2019b;Zhang et al 2019;Planas-Clarke et al 2020) and manipulation experiments (Dise, Gorham, and Verry 1993;Funk et al 1994;Aerts and Ludwig 1997;Blodau, Basiliko, and Moore 2004;Strack and Waddington 2007;Turetsky et al 2008;Chivers et al 2009;Dinsmore et al 2009;Laine et al 2009;Pearson et al 2015;Olefeldt et al 2017;Kang et al 2018;…”
Section: Effects Of Water Level Alteration On Ch 4 Emissionsmentioning
confidence: 84%
“…There is so far no general agreement on the response of total plant production to water level alteration. Decreased plant production in peatlands has been reported if water levels decline, especially during the growing season (Bubier et al 2003;Chimner and Cooper 2003a;Blodau, Basiliko, and Moore 2004;Chivers et al 2009;Lund et al 2012;Churchill et al 2015;Potvin et al 2015;Chimner et al 2016;Olefeldt et al 2017;Kang et al 2018), which is related to increased water stress (Alm et al 1999;Griffis, Rouse, and Waddington 2000;Weltzin et al 2000). Rewetting via hydrologic restoration can lead to an increase in production for increasing the production of dominant species that favors wetter conditions (Maanavilja et al 2015;Karki et al 2016), although drying can also increase plant production if the production of trees and shrubs increases (Sulman et al 2009(Sulman et al , 2012Munir et al , 2015Järveoja et al 2016;Kasimir et al 2018;Ratcliffe et al 2019).…”
Section: Effects Of Water Level Alteration On Primary Productionmentioning
confidence: 99%
“…The experimental results showed that when the soil moisture was less than 15% or more than 40%, the carbon dioxide absorption rate was lower, and when the soil moisture content was 20-40%, the carbon dioxide absorption rate would increase and CH 4 emission was strong, but the overall impact on CO 2 was stronger. Therefore, extreme dry weather in the future may make the plateau a carbon source [63]. However, extreme weather is generally a short-term weather situation.…”
Section: Whether To Consider Frozen Soil Experimental Scenario Main Imentioning
confidence: 99%
“…In recent years, due to the aggravation caused by human activities, the global atmospheric and water cycle pattern has been significantly changed, resulting in an increasing frequency and intensity of global extreme climate events (IPCC, 2013;Kreyling et al, 2008;Kang et al, 2018;Thakur et al, 2017). Recent studies have indicated that the occurrence of extreme drought events can significantly change the water and heat conditions of the ecosystem, affecting the physiological state of plants and activities of soil microbes, triggering changes in the soil structure and function, and breaking the original carbon balance of the ecosystem, which in turn can aggravate the intensity and frequency of extreme drought events on a global scale (Reichstein et al, 2013;Bloor & Bardgett, 2012;Beierkuhnlein et al, 2011;Hao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%